NEW APPROACHES IN THE TREATMENT AND PREVENTION OF RECURRENT OBSTRUCTIVE BRONCHITIS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
In a study of children with recurrent obstructive bronchitis, the effectiveness of inhaled beclamethasone was established. 54 patients with recurrent obstructive bronchitis were examined. The study showed that patients receiving inhaled beclomethasone experienced statistically significant positive dynamics in clinical symptoms, improvement in E:I index starting from the 3rd day of treatment by an average of 0.24-0.37 (P